Social Media Usage by Entrepreneurs – A review paper - Chhetia, Kirtika (The journal of contemporary issues in business and government, 2021)
This paper aims to build a review of the literature on the field of Entrepreneurs in business. This literature review will provide an archive of past research points and methodologies related to the studies of the reach and engagement that affect the use of social media for entrepreneurs to explore, analyse and develop a clear understanding of the different research topics and methodologies implemented in published articles. The paper also tries to understand the researches done on Women Entrepreneurs and try to find a research gap combining the two phenomena.